FOOD AND FEEDING HABITS OF THE SPOTTED HERRING, HERKLOTSICHTHYS PUNCTATUS (RUPPELL) FROM THE ANDAMAN SEA - Marichamy, R (Indian Journal of Fisheries, 2011)
Clupeids being economically important food fishes in India, their food and feeding habits have been investigated in detail by many workers. Special mention may be made of the investigations on Sardlnella longiceps (Hornell and Nayudu, 1924; Nair, 1953; Dhulkhed, 1962), Sardinella gibbosa JDey/anesan, 1932; Ganapati and Rao 1957), Kowala coval (Na.it, 1951), Thrissocles mystax, (Venkataraman, 1956), Raconda russellina (Va.T^e&e, 1961) and Coilia feorneenjij (Varghese, 1961). However, practically no information is available on the food and feeding habits of Herklotsichthys punctatus (Ruppel) a clupeid \^’hich is commercially important in the waters around Andaman Islands. A detailed study on the biology of H. punctatus was undertaken during the years 1965-67 and the present account relates to the food and feeding habits of this species. .